1996
DOI: 10.1111/j.1530-0277.1996.tb01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Cytokine‐inducible Transcription Factors

Abstract: Cytokines, such as TNF alpha, modulate the behavior of many cells by regulating the expression of a wide array of genes. When a cytokine binds to its receptor on the cell surface, the receptor becomes activated and activates signal transduction cascades. These cascades typically involve a series of phosphorylation reactions that lead to sequential activation of various kinases. The targets of these kinases include DNA binding proteins that regulate the transcription of target genes. The activity of DNA binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 31 publications
7
42
1
3
Order By: Relevance
“…Exposure to ethanol for 16 h increased the basal JNK activity but there was no change in agonist-induced JNK activation. Whereas chronic ethanol intake for 60 days inhibited the activation of ERK, p38, and JNK induced either by partial hepatectomy or by treatment with various agonists (Zeldin et al, 1996;Chen et al, 1998). In the present study, we observed that acute ethanol treatment for 5-10 min inhibited growth factor-stimulated tyrosine phosphorylation and ERK activation even in the absence of any preincubation with ethanol.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Exposure to ethanol for 16 h increased the basal JNK activity but there was no change in agonist-induced JNK activation. Whereas chronic ethanol intake for 60 days inhibited the activation of ERK, p38, and JNK induced either by partial hepatectomy or by treatment with various agonists (Zeldin et al, 1996;Chen et al, 1998). In the present study, we observed that acute ethanol treatment for 5-10 min inhibited growth factor-stimulated tyrosine phosphorylation and ERK activation even in the absence of any preincubation with ethanol.…”
Section: Discussionsupporting
confidence: 60%
“…The blockage of growth factor-mediated cell proliferation by ethanol in several systems elicits the hypothesis that growth factor-induced signaling processes are targets of ethanol toxicity. Included are adenylate cyclase (Hoek et al, 1992;Williams and Kelly, 1993), protein kinase C (Pandy, 1996), protein tyrosine kinases (Miyakawa et al, 1997, Resnicoff et al, 1993, Thurston and Shukla, 1992, MAPKs (Roivainen et al, 1995;Reddy and Shukla, 1996;Chen et al, 1998;Tombes et al, 1998;Reddy and Shukla, 2000), phospholipase C and D (Higashi and Hoek, 1991;Hoek et al, 1992;Thurston and Shukla, 1992;Saso et al, 1997;Zhang and Farrell, 1999), transcription factors such as NF-κB (Zeldin et al, 1996) and STAT3 (Chen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…JNK Immune Complex Assay-Jnk-1 activity was evaluated as we have described (15,23). Briefly, antibodies for Jnk-1 (Santa Cruz Diagnostics) were used to immunoprecipitate Jnk-1 from hepatic nuclear extracts; the Jnk-1 substrate, GST-c-Jun fusion peptide (Santa Cruz Diagnostics) and [␥- After separating the reaction products by electrophoresis on 10% acrylamide gels and transfer to nylon membranes by capillary blotting, Jnk-1 activity was quantified by PhosphorImager analysis of the phosphorylated substrate using ImageQuant software (Molecular Dynamics, Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Ethanol modulates the activity of several important signaling molecules (32) including ERK1/2, p38 MAPK (33), JNK (33,34), and the transcription factors NFB (35) and Egr-1.…”
mentioning
confidence: 99%